The therapeutic efficacy of resveratrol for acute lung injury—A meta−analysis of preclinical trials - Tang, Yin; Fu, Wenqiao; Wei, Ke; Liu, Ling; Wu, Siqi; Tang, Wenjing (Frontiers in Pharmacology, 2022)
Background: Resveratrol (RES) has a protective effect on acute lung injury (ALI) or acute respiratory distress syndrome (ARDS). Our purpose was to conduct a meta-analysis to investigate the efficacy of RES for ALI/ARDS in animal models. Methods: PubMed, EMBASE and Web of Science were searched to screen relevant preclinical trials. The standardized mean difference (SMD) was used to compare the lung injury score, lung wet-dry weight ratio (W/D ratio), tumor necrosis factor-α (TNF-a), interleukin-1β (IL-1β), IL-6, IL-10, the number of neutrophils in bronchoalveolar lavage fluid (BALF) and the total protein in BALF between the treatment and control group. SYRCLE’s risk of bias tool was used for quality assessment. Results: A total of 17 studies published from 2005 to 2021 were included in our study to calculate the SMD with corresponding confidence interval (CI). As compared with controls, RES significantly decreased the lung injury score (SMD −2.06; 95% CI −2.77, − 1.35; p < 0.00001) and W/D ratio (SMD −1.92; 95% CI −2.62, −1.22; P < 0.00001). RES also reduced the number of neutrophils in BALF (SMD −3.03; 95% CI −3.83, −2.24; P < 0.00001) and the total protein in BALF (SMD −5.59; 95% CI −10.10, −1.08; P =0.02). Furthermore, RES was found to downregulate proinflammatory mediators such as TNF-a (SMD −2.02; 95% CI −3.09, −0.95; p =0.0002), IL-1β (SMD -2.51; 95% CI -4.00, -1.02; p = 0.001) and IL-6 (SMD -2.26; 95% CI -3.49, -1.04; p = 0.0003). But RES had little effect on the anti-inflammatory mediators such as IL-10 (SMD 2.80; 95% CI −0.04, 5.63; p =0.05). Sensitivity analysis and stratified analysis were performed for the outcome indicators with heterogeneity. Conclusions: RES treatment is effective on reducing the severity of ALI. However, more animal studies and human trials are needed for further investigation. Our study may provide a reference for preclinical and clinical studies in the future to some extent.